A prospective evaluation of the fourth national Be Clear on Cancer 'Blood in Pee' campaign in England. (15th May 2022) - Merriel, Samuel William David; Ball, Susan; Bright, Chloe Jayne; Mak, Vivian; Gildea, Carolynn; Paley, Lizz; Hyde, Chris; Hamilton, William; Elliss‐Brookes, Lucy
Abstract: Objective: To assess the impact of the fourth Be Clear on Cancer (BCoC) 'Blood in Pee' (BiP) campaign (July to September 2018) on bladder and kidney cancer symptom awareness and outcomes in England. Methods: In this uncontrolled before and after study, symptom awareness and reported barriers to GP attendance were assessed using panel and one‐to‐one interviews. The Health Improvement Network (THIN), National Cancer Registration and Analysis Service (NCRAS) and NHS Cancer Waiting Times (CWT) data were analysed to assess the impact on GP attendances, urgent cancer referrals, cancer diagnoses and 1‐year survival. Analyses used Poisson, negative binomial and Cox regression. Results: Symptom awareness and intention to consult a GP after one episode of haematuria increased following the campaign. GP attendance with haematuria (rate ratio (RR) 1.17, 95% confidence interval (CI): 1.07–1.28) and urgent cancer referrals (RR 1.18 95% CI: 1.08–1.28) increased following the campaign. Early‐stage diagnoses increased for bladder cancer (difference in percentage 2.8%, 95% CI: −0.2%–5.8%), but not for kidney cancer (difference −0.6%, 95% CI: −3.2%–2.1%). Conclusions: The fourth BCoC BiP campaign appears to have been effective in increasing bladder cancer symptom awareness and GP attendances, although long‐term impacts are unclear.